Multisite study of Aggressive Behavior Risk Assessment Tool in emergency departments - Son Chae Kim; Jennifer Kaiser; Julie Bulson; Tracy Hosford; Ashleigh Nurski; Carol Sadat; Nicole Kalinowski (Journal of the American College of Emergency Physicians Open)
Abstract Objective Violence is a major preventable problem in emergency departments (EDs), and validated screening tools are needed to identify potentially violent patients. We aimed to test the utility of the Aggressive Behavior Risk Assessment Tool (ABRAT) for screening patients in the ED. Methods A prospective cohort study was conducted among adult and pediatric patients aged ≥10 years visiting 3 emergency departments in Michigan between May 1, 2021, and June 30, 2021. Triage nurses completed the 16‐item checklist using electronic health records (EHRs), and the occurrence of violent incidents were collected before ED disposition. A multivariate logistic regression model was applied to select a parsimonious set of items. Results Among 10,554 patients, 127 had ≥1 violent incidents (1.2%). The regression model resulted in a 7‐item ABRAT for EDs, including history of aggression and mental illness and reason for visit, as well as 4 violent behavior indicators. Receiver operating characteristics analysis showed that the area under the curve was 0.91 (95% confidence interval [CI], 0.87–0.95), with a sensitivity of 84.3% (95% CI, 76.5%–89.9%) and specificity of 95.3% (95% CI, 94.8%–95.7%) at the optimal cutoff score of 1. An alternative cutoff score of 4 for identifying patients at high risk for violence had a sensitivity and specificity of 70.1% and 98.9%, respectively. Conclusion The ABRAT for EDs appears to be a simple yet comprehensive checklist with a high sensitivity and specificity for identifying potentially violent patients in EDs. The availability of such a screening checklist in the EHR may allow rapid identification of high‐risk patients and implementation of focused mitigation measures to protect emergency staff and patients.